BEYOND INTENTIONS: UNDERSTANDING THE IMPACT OF VALUE CO-CREATION ON DEPOSIT WASTE SEGREGATION - Aditya, Dana; Mustikorini, Dwi Indah; Tamonsang, Matheous (International Journal of Social Service and Research, 2024)
This study examines the factors influencing the intention to segregate waste and participate in waste bank programs, based on the Theory of Planned Behavior (TPB) and the concept of value co-creation. The research highlights the significant role of attitudes, subjective norms and perceived behavioral in shaping the intention to segregate waste. However, it finds that attitudes, subjective norms and perceived behavioral control did not significantly influence the intention to segregate waste. This suggests that participants' decisions to engage in waste management practices were less affected by their attitudes, subjective norms and perceived control over the behavior. Furthermore, value co-creation was found to mediate the relationship between attitudes and intentions, indicating that when consumers actively contribute to creating value, they become more motivated to continue their pro-environmental behaviors. The study also reveals that positive experiences and a sense of ownership in the waste management process reinforce participants' commitment to segregating waste, even without external pressure or rewards. The findings provide valuable insights into how programs involving active participation in co-creating value can enhance environmental behaviors.